Pengaruh Waktu Inokulasi Terhadap Laju Infeksi Penyakit Bean Common Mosaic Virus (BCMV) pada Tanaman Kacang Panjang (Vigna Sinensis L.) - KARISMAYATI, I GUSTI AYU; WIRYA, GUSTI NGURAH ALIT SUSANTA; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
The Effect of Inoculation Time towards the Infection Rate of Bean Common Mosaic Virus (BCMV) Disease on Long Beans (Vigna sinensis L.) Bean Common Mosaic Virus (BCMV) is kind of disease which greatly decrease the production of beans. The information about the spread of this disease is unknown. Therefore, it should be a research to be investigated. The purpose of the study is to determine the effect of inoculation time towards the infection rate of BCMV disease on long beans. The study uses a Randomized Complete Block Design (RCB) consisted of eight treatments and four replications, namely: the treatment of plants which originated from infected seeds of BCMV, inoculated at the age of 2, 3, 4, 5, 6, and 7 week after planting, and without inoculation as a control.The results showed that the younger of long beans infected by BCMV, resulting in the higher infection rate of disease and the symptoms caused would be more severe. The infection rate on plants which were inoculated at the age of 2, 3, 4, 5, 6, 7 week after planting and without inoculation were respectively 0,85; 0,77; 0,73; 0,49; 0,36; 0,31; and 0. The inoculation treatments at the age of 2, 3, and 4 week after planting were highly vulnerable to be infected by BCMV and caused the symptoms of severe mosaic, severe leaf malformations, and thickening of the bone leaves, whereas the inoculation treatments at the age of 5, 6, and 7 week after planting were resistant against BCMV disease with symptoms caused were moderate to mild, while the treatments without inoculation did not show any infection symptoms of BCMV.
Keywords: Long beans, Bean Common Mosaic Virus, Infection rate